Hippocampal cognitive and relational map paradigms explored by multisensory encoding recording with wide-field calcium imaging - Dechuan Sun; Noor E. Karishma Shaik; Ranjith Rajasekharan Unnithan; Chris French (iScience, 2024)
Summary: Two major theories have been proposed to explain hippocampal function: cognitive map and the relational theories. They differ in their views on whether hippocampal neurons can process non-spatial information independently. However, the explanatory power of these theories remains unresolved. Additionally, more complex aspects of hippocampal neural population responses to non-spatial stimuli have not been investigated. Here, we used miniaturized fluorescence microscopy to investigate mouse CA1 responses to spatial, visual, auditory modalities, and combinations. We found that while neuronal populations primarily processed spatial information, they also showed strong sensitivity to non-spatial modalities independent of spatial inputs, exhibiting distinct neuronal dynamics and coding patterns. These results provide strong support for the relational theories.